Wi-Fi Signal Propagation Modeling - Rakhmanov, Sergey V.; Loktev, Daniil A. (International Youth Conference on Radio Electronics, Electrical and Power Engineering (REEPE ...) (Online), 2025)
The advent of Wi-Fi technology has become imperative in contemporary society, as it facilitates wireless Internet access, and enables the integration of devices into a networked system. The pervasive implementation of Wi-Fi in residential apartments, office buildings, cafes, railway stations has engendered a multitude of novel scenarios that facilitate the utilization of this technology. A particularly salient area of research in this domain pertains to the use of Wi-Fi for determining the presence of individuals, estimating their number, and even ascertaining their poses and gestures. This subject has recently garnered significant attention from the scientific community. The accelerated proliferation of Wi-Fi necessitates the undertaking of studies that explore the propagation models of Wi-Fi signals. The present paper aims to provide a comprehensive overview of the existing models of radio signal propagation, a critical analysis of their respective strengths and limitations, and the proposal of a methodology for modeling Wi-Fi signal propagation. This objective is pursued by leveraging the wave equation and a range of mathematical modeling techniques, including the finite difference method and the finite element method.